2021
DOI: 10.1093/icvts/ivab322
|View full text |Cite
|
Sign up to set email alerts
|

Results of concomitant cryoablation for atrial fibrillation during mitral valve surgery

Abstract: OBJECTIVES Concomitant atrial fibrillation ablation during mitral valve (MV) surgery using radio frequency energy sources has been reported previously with excellent outcomes. However, data regarding the effectiveness of concomitant cryoablation remain limited. This study aimed to assess the efficacy of concomitant cryoablation in patients scheduled for MV surgery. METHODS Between 2012 and 2020, 242 adult patients who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The weighted mean duration of AF preoperatively was 50 months (95% CI: 46.1–53.9), and weighted mean ejection fraction (EF) of 55.5% (95% CI: 53.7–57.1%). The weighted mean LA diameter was 55.7 mm (95% CI: 42.5–59.1) and four studies reported a mean LA diameter greater than 60 mm ( 19 , 21 , 29 , 50 ). These results are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The weighted mean duration of AF preoperatively was 50 months (95% CI: 46.1–53.9), and weighted mean ejection fraction (EF) of 55.5% (95% CI: 53.7–57.1%). The weighted mean LA diameter was 55.7 mm (95% CI: 42.5–59.1) and four studies reported a mean LA diameter greater than 60 mm ( 19 , 21 , 29 , 50 ). These results are summarized in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“….7 mm (95% CI: 42.5-59.1) and four studies reported a mean LA diameter greater than 60 mm(19,21,29,50). These results are summarized in Table2.…”
mentioning
confidence: 84%
“…Aortic clamping time, CPB time, and postoperative complications were consistent with reports from other authors worldwide. 16,19,20 By specifically choosing patients at low or intermediate risk for minimally invasive procedures, we have established a safe population for these technically advanced surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the NSR of antiarrhythmic medications (79%, 84%, and 82%, respectively), they discovered that a high return to normal sinus rhythm (NSR) was recorded at 6, 12, and 24 months (92%, 91%, and 86%, respectively) ( 39 ). Bogachev-Prokophiev et al also showed that concomitant AF cryoablation with mitral valve surgery provided an acceptable level of abstinence from recurrent atrial arrhythmias throughout long-term monitoring ( 40 ). These studies suggest that during mitral valve surgery, concurrent cryoablation is a safe and reliable procedure and can be used as a safe and effective treatment for patients with AF combined with mitral valve disease.…”
Section: Surgical Ablation Technologymentioning
confidence: 99%